Research progress and development tendency of polymer drilling fluid technology for unconventional gas drilling - He, Yinbo; Jiang, Guancheng; Dong, Tengfei; Wang, Guoshuai; He, Jing; Dou, Huanjun; Du, Mingliang (Frontiers in Energy Research, 2023)
Unconventional gas includes tight sandstone gas, shale gas, coalbed methane and natural gas hydrate, etc. With huge reserves, unconventional gas has become the most important natural gas resource successor after the end of the “EASY OIL” era. Drilling fluid is an indispensable wellbore working fluid for unconventional gas drilling with multiple functions. Polymer drilling fluid (PDF) is the most common, longest developed and most diverse drilling fluid type. With advantages of easily-controlled rheology, convenient on-site performance maintenance especially low cost and weak environment pollution, PDF is gradually replacing oil-based drilling fluid as the first choice for unconventional gas drilling. The invention of non-disperse low-solid-content PDF in 1960s marks that PDF technology has entered the stage of scientific development, until now its development has generally experienced five stages: beginning, developing, improving, re-developing and re-improving. Dozens of polymer additives and PDF systems have been invented and applied, which have solved severe drilling problems, improved greatly drilling efficiency and promoted exploration and development on difficult oil and gas resources. This paper firstly reviews the research progress of PDF technology according to the timeline by introducing the composition, feature, advantages and disadvantages of some representative polymer additives and PDF system, emphatically the function and mechanism of stabilizing wellbore, lubricating drilling tools and protecting reservoir of biomimetic wellbore-strengthening PDF and amphiphobic high-efficiency PDF in unconventional gas drilling. Then combining future global especially China’s strategical needs of oil and gas exploration and development, the development tendency of PDF technology is critically illustrated by introducing several potential research directions.